Forming Early Children's Character Through School Culture In The Industry Revolution 4.0 - Hisam Ahyani (Raudhatul Athfal: Jurnal Pendidikan Islam Anak Usia Dini, 2021)
The importance of cultivating children's character from an early age in the era of Industrial Revolution 4.0 as it is today through Bidaya schools because this aims to create a young generation who is superior, intelligent, competent, quality, has responsibility and has good character according to the ideals of the nation in facing every era which keeps changing. For that we need special ways / steps in building character in early childhood. Raudhatul Athfal (RA) Al-Azhar Citangkolo, Banjar City is very important to offer a character education model through a superior school culture. The research method used in this study is qualitative with 15 children as the research subjects. Collecting data through interviews, and observations, and documentation. The results showed that in building children's character in Raudhatul Athfal (RA) Al-Azhar Citangkolo, Banjar City, West Java, the era of Industrial Revolution 4.0 could be done through school culture, namely by instilling habituation and exemplary by teachers, schools and parents at home to children include: 1) instilling an attitude of honesty to children, 2) instilling an attitude of responsibility in children, 3) instilling discipline in children, 4) instilling cooperation